1983
DOI: 10.1161/01.cir.67.2.330
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of patients with acute pulmonary edema and normal ejection fraction after acute myocardial infarction.

Abstract: SUMMARY To assess the prognostic importance of resting left ventricular function in survivors of acute myocardial infarction with pulmonary edema, we retrospectively identified 39 consecutive patients who presented with acute pulmonary edema and myocardial infarction. Sixteen patients had radionuclide ejection fractions 10 2 days postinfarction of > 0.45 (group A, mean 0.55 0.06), and 23 patients had ejection fractions S 0.45 (group B, 0.32 + 0.06). There were no significant differences between the two groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…but the 1-vear mortality increased significantly with increasing Killip class (table 1), suggest ing that patients in the worst Killip class (III and IV) are at higher risk than patients in Kil lip class II despite the lack of difference in WMI on day 5. This is in accordance with pre vious studies, where patients with severe clin ical heart failure in the course of AMI formed a high risk group, despite the finding of a good resting LVEF at the time of discharge [22,23]. The patients with a good resting LVEF who present themselves in Killip class III or IV might be patients with remote myocardial dysfunction or myocardial stunning [10].…”
Section: Discussionsupporting
confidence: 89%
“…but the 1-vear mortality increased significantly with increasing Killip class (table 1), suggest ing that patients in the worst Killip class (III and IV) are at higher risk than patients in Kil lip class II despite the lack of difference in WMI on day 5. This is in accordance with pre vious studies, where patients with severe clin ical heart failure in the course of AMI formed a high risk group, despite the finding of a good resting LVEF at the time of discharge [22,23]. The patients with a good resting LVEF who present themselves in Killip class III or IV might be patients with remote myocardial dysfunction or myocardial stunning [10].…”
Section: Discussionsupporting
confidence: 89%
“…Thus, in AMI it has been shown that discrepancies between subjective and objec tive measures of left ventricular function are not infrequent [5,[16][17][18], Therefore, it has been claimed that signs of clinical heart fail ure must be corroborated with objective measurements of left ventricular function to confirm a diagnosis of congestive heart fail ure [ 14], Gadsboll et al [ 19] found consider able interobserver variability in the evalua tion of clinical signs of heart failure in the 2nd week after AMI. Further confounding for the clinical evaluation is the fact that signs and symptoms of clinical heart failure may fluctuate over time and with treatment [20], Contrary, left ventricular systolic per formance appears to be an earlier and more stable marker of risk in the setting [5],…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have examined the relationship between survival and particular clinical signs of congestive heart failure (CHF) (in particular, the prognosis is poor for NYHA class IV patients), relatively few information is available as regards the survival of CHF patients who in the course of their illness have at some time been hospitalized with acute pulmonary edema (APE) [1][2][3][4][5]. In this study we investigated the clinical characteristics and survival of this group of patients and of subgroups defined by the etiology of their cardiopathy, and compared them with the characteristics and survival of CHF patients without APE.…”
Section: Introductionmentioning
confidence: 99%